Different faces of passion in the context of leadership = Różne oblicza pasji w kontekście przywództwa - Kozłowski, Rafał (Zielona Góra: Faculty of Economics and Management Press)
The paper describes passion, which depending on the context, may motivate entrepreneurial leaders not only to found an organization, but also to grow and expand their ventures. It should also be noted that there is also the dark side of passion dominated by greed and hubris, which may result in counterproductive outcomes.
Keywords: przywództwo; przedsiębiorczość; pasja; leadership; entrepreneurship; passion